THE SCOPE OF GLOBALIZATION AND ITS IMPACT ON THE ECONOMIC AND FINANCIAL-BANKING SECTOR - ALEXANDRU OLTEANU (Challenges of the Knowledge Society, 2011)
Currently, on the grand scene of social-human life, we may encounter all possible social players … Should we follow “movement” as a fundamental social and historical phenomenon, we shall find that the world has become, to a large extent, a single societal system, as a result of the development of interdependence connections affecting each and every one of us. The envisaged global system is not just an environment within which particular societies develop and evolve, as separate systems. Through the social, economic, financial and political ties, through the communication systems crossing interstate borders, it turns into a new system, with a trend towards materially restraining the action of its subsequent systems, decisively containing the fate of those living in each of them. The general term used to characterize this increasing interdependence of the human society is that of globalization.